Points of view: arrestees’ perspectives on police body-worn cameras and their perceived impact on police–citizen interactions - Taylor, Emmeline (The British journal of criminology, 2019)
Entirely absent from debates about the desirability and potential impacts of police body-worn cameras (BWCs) are the views of a significant group on the other side of the lens—individuals who have recently experienced arrest by a police officer. In a bid to redress this significant gap, this article reports findings from the first study to examine arrestee views and experiences of police BWCs. Data from interviews with 907 police detainees reveal that they are largely in favour of officers wearing cameras, believing that they can provide greater accountability and improve the behaviour of both law enforcement officers and members of the public. Importantly, however, this support is contingent on a number of operational and procedural policies regulating the use of BWCs.